2016
DOI: 10.1021/acs.langmuir.6b02575
|View full text |Cite
|
Sign up to set email alerts
|

3D-Membrane Stacks on Supported Membranes Composed of Diatom Lipids Induced by Long-Chain Polyamines

Abstract: Long-chain polyamines (LCPAs) are intimately involved in the biomineralization process of diatoms taking place in silica deposition vesicles being acidic compartments surrounded by a lipid bilayer. Here, we addressed the question whether and how LCPAs interact with lipid membranes composed of glycerophospholipids and glyceroglycolipids mimicking the membranes of diatoms and higher plants. Solid supported lipid bilayers and monolayers containing the three major components that are unique in diatoms and higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 61 publications
3
21
1
Order By: Relevance
“…Such similar rates of diffusion imply that the two membranes in the double membrane patches are interconnected via a lipid phase. Similar patches of membrane stacks that are connected to an underlying bilayer have previously been observed after the addition of lipopolysaccharide and, very recently, long chain polyamines …”
Section: Resultssupporting
confidence: 75%
“…Such similar rates of diffusion imply that the two membranes in the double membrane patches are interconnected via a lipid phase. Similar patches of membrane stacks that are connected to an underlying bilayer have previously been observed after the addition of lipopolysaccharide and, very recently, long chain polyamines …”
Section: Resultssupporting
confidence: 75%
“…Several preliminary experiments were performed to optimize the lipid composition and buffer conditions for the thylakoid liposomes in order to achieve a high-quality, contiguous supported lipid bilayer comparable to those of 100% DOPC. After initial tests with either the native mixture of thylakoid lipids or 100% DGDG were unsuccessful, 25% DOPC was incorporated into the thylakoid lipid mixture to promote formation of planar bilayers [ 44 ] which are amenable to surface-based work. This gave a final adapted mixture comprised 35% MGDG, 20% DGDG, 12% SQDG, 8% Soy PG, 25% DOPC (w/w%).…”
Section: Resultsmentioning
confidence: 99%
“…Proteoliposomes containing LHCII and thylakoid lipids are stable due to the inherent curvature of a vesicle and are becoming the standard for in vitro studies of NPQ in solution [ 27 , 40 , 41 , 43 , 66 , 75 , 76 ], however, proteoliposomes are not conducive to high resolution imaging. Few studies have achieved the formation of planar bilayers of thylakoid lipids on a solid support as required for high resolution microscopy, due to the high curvature of MGDG [ 44 ]. We have demonstrated that it is possible to generate membranes including LHCII with thylakoid lipid mixtures on solid supports, and found similar protein rearrangements and similar intermediate levels of quenching as when using DOPC phospholipids ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary interaction. A recent experimental study [33] focused on the influence of the boundary of the SDV on the aggregation of biomolecules. In particular, the interaction of long-chain polyamines with lipid membranes was analyzed.…”
Section: D Simulationsmentioning
confidence: 99%